Metal-semiconductor transition in CuS-Cu1.8S mixed phase thin films. (February 2015) - Ren, Bing; Wang, Lin; Huang, Jian; Tang, Ke; Yang, Yimin; Wang, Linjun
Abstract: We report the semiconducting behavior at room temperature and a metal-semiconductor transition (MST) at lower temperature in copper sulfides (Cu x S) thin films. Cu x S thin films, deposited by direct magnetron sputtering technique, are found to be of CuS-Cu1.8 S mixed phase by XRD. The deposited films exhibit low electrical resistivity close to ∼10 −4  Ω cm at room temperature and free-carrier absorption in the near infrared (NIR) region due to excess holes in the valence band. Temperature dependent resistivity measurements show the MST at ∼260 K, to the best of our knowledge, for the first time. The temperature dependent metal-semiconductor transition is attributed to the phase transition from Cu1.8 S to CuS at T c during the cooling process. This work could help give insight into the transport characteristics as well as phase transition at lower temperature in copper sulfides thin films. Highlights: CuS-Cu1.8 S mixed phase films were grown on quartz by sputtering technique. As-deposited films exhibit free-carrier absorption in the near infrared (NIR) region. Metal-semiconductor transition (MST) were observed in as-deposited Cu x S thin films. To the best of our knowledge, it is the first time to report an MST in Cu x S films. MST phenomena observed are attributed to a phase transition from Cu1.8 S to CuS.